Referral pathways for reperfusion of STEMI – developing strategies for appropriate intervention - Snyders, Adriaan; Delport, Rhena (SA Heart Journal, 2017)
The SA Heart Association seeks to to improve the early management of ST-segment elevation myocardial infarction in South Africa. This pilot study was undertaken to establish the current time intervals present in the referral pathways to percutaneous coronary intervention (PCI) facilities in the Tshwane Metropole and to further identify the barriers to appropriate management of STEMI. Method: Cardiologists from 5 PCI-capable hospitals recruited the patients in the catheterisation laboratory and captured the data. Interviews were conducted with three emergency medical services (EMS) to assess paramedics’ scope of practice and identify hindrances to the effective management of STEMI patients. Results: Median system delays were longer in patients requiring inter-facility transport (IFT; n=29) compared to patients with direct access to a PCI facility (DA) patients (median 3.7 vs. 30.4 hours; p<0.001). Door-toballoon times of ≤90 minutes were achieved in only 22% DA and 33% IFT patients. Fibrinolysis within ≤30 minutes was achieved in 50% DA and 20% IFT patients. Reperfusion was attempted in <12 hours of symptom onset in signifi cantly more DA than IFT patients (70% vs. 34%; p=0.012 respectively). Paramedics were suitably trained and ambulances reasonably equipped to manage STEMI patients. However, members of the public do not routinely summon EMS. Conclusion: Education initiatives and improved systems of care have the potential to improve STEMI patient outcome in South-Africa.